Needs assessment of information and communication technology literacy (ICT literacy) of students in secondary educational service area - Thammasaeng, Patcharapon; Pupat, Phadungchai; Petchaboon, Sawas (My University, 2016)
The objectives of this research were (1) to study authentic situations of Information Communication Technology literacy of students in secondary educational service area (2) to compare situations of ICT literacy of students in secondary educational service area, divided in each levels (3) to examine need assessment of ICT literacy of students in secondary educational service area (4) to prioritise needs assessment of ICT literacy of students in secondary educational service area. The sample consisted of 340 ICT teachers, teaching in Grade 7 to 9 from schools in secondary educational service area in 2015. The sampling group was drawn from 2,343 ICT teachers by using multi-stage sampling technique. Data were collected by using questionnaire, in order to collect data of expected and authentic situations of students understanding about ICT. The questionnaires include 76 questions from 7 components in which the questionnaires were approved content validity from experts at level of 0.98 and 0.99, respectively. The statistics were used to analyse the data as follows: mean (M), standard deviation (SD), one-way ANOVA, Matrix analysis, priority needs index modified (PNI modified). The study revealed that (1) authentic situation of ICT literacy of students in secondary educational service area was found at "Moderate" level (2) authentic situation of ICT literacy of students in secondary educational service area, divided in levels was found "No different" (3) authentic situation of need assessment in 7 aspects (Define, Access, Manage, Evaluate, Integrate, Create and Communicate) fell in the third quadrant, in which means "Need to be improved" (4) prioritise need assessment from the most necessary to the least was found as follows: Manage, Evaluate, Create, Define, Access, Integrate and Communicate, respectively.
Keywords: ICT; ICT literacy; Need assessment